Establishment of State Epidemic Intelligence Unit: From Thought to Action - J K Kosambiya (Indian Association of Preventive and Social Medicine, 2022)
Public Health Emergencies of International Concern (PHEIC) have always been a threat to the health care system regardless of level (country, state or district). [1,2] The year 2020 will always be remembered for one of the biggest pandemics in the history of mankind. Gujarat, like other states of India, was challenged by the COVID-19 pandemic. In the Department of Community Medicine, Government Medical College, Surat, Gujarat, we were forecasting the course of COVID-19 wave in Surat city and Surat District using modeling techniques. It was during this activity that we became acutely aware that there was an unmet need of big data collection and analysis, especially at State level.